Reflections on Bioethics - Antonio Morales-González, José; Eugenia Aguilar Nájera, María (IntechOpen, 2018)
The book Reflections on Bioethics is an effort that brings together works grouped into five sections: "Bioethics and Health", "Bioethics and Education", "Bioethics and Technology", "Bioethics in the Use of Experimental Animals",and "Selected Topics of Bioethics". In each of these sections, the fundamental concepts of bioethics and their relationship with each of these branches of knowledge are covered. The purpose is to give the reader a specific document of topics, it is not intended to be a treaty because the study of any of the five sections is very broad. However, this is an effort that manages to combine in interdisciplinary subjects that are fundamental for professionals of all fields of knowledge.